Cytoarchitectonic Mapping of MRI Detects Rapid Changes in Alzheimer's Disease - Blair, Jamie C.; Lasiecka, Zofia M.; Patrie, James; Barrett, Matthew J.; Druzgal, T. Jason (Frontiers in Neurology, 2020)
Clinical and pathological progression of Alzheimer’s disease often proceeds rapidly, but little is understood about its structural characteristics over short intervals. This study evaluated the short temporal characteristics of brain structure in Alzheimer’s disease through application of cytoarchitectonic probabilistic brain mapping to measurements of grey matter density, a technique which may provide advantages over standard volumetric MRI techniques. Grey matter density was calculated using voxel-based morphometry of T1-weighted MRI obtained from Alzheimer’s patients and healthy controls evaluated at intervals of 0.5, 1.5, 3.5, 6.5, 9.5, 12, 18, and 24 months by the MIRIAD study. Alzheimer’s patients had 19.1% less grey matter at 1st MRI, and declined 81.6% faster than healthy controls. Atrophy in the hippocampus, amygdala, and basal forebrain distinguished the Alzheimer’s patients. Notably, the CA2 of the hippocampus was found to have atrophied significantly within one month. Grey matter density measurements were reliable, with intraclass correlation coefficients exceeding 0.8. Comparative atrophy in the Alzheimer’s group agreed with manual tracing MRI studies of Alzheimer’s while identifying atrophy on a shorter time scale than has previously been reported. Cytoarchitectonic mapping of grey matter density is reliable and sensitive to small-scale neurodegeneration indicating its use in future study of Alzheimer’s disease.